2004
DOI: 10.1583/1545-1550(2004)011<0089:etitmo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Techniques in the Management of Acute Arterioenteric Fistulas

Abstract: Endovascular application of covered stents provides an alternative treatment, avoiding extensive surgery. In cases of neoplastic erosion of a large vessel, endovascular stenting can offer a palliative solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…11 These endografts have other applications, such as pseudoaneurysms, traumatic arterial perforations, arteriovenous communications, and even arterioureteral fistulae. 12 This endovascular treatment was effective and safe in our cases, with a very short hospitalization, no perioperative complications, and good results after 1-year followup. We chose stent-graft repair in our patients for the following reasons: the aneurysmal deterioration was restricted to a limited, short portion of the allograft; the anastomosis was not involved; the aneurysmal dilatation was at a distance from the flexion area of the knee; and there were no biological or clinical signs of infection.…”
Section: Discussionmentioning
confidence: 52%
“…11 These endografts have other applications, such as pseudoaneurysms, traumatic arterial perforations, arteriovenous communications, and even arterioureteral fistulae. 12 This endovascular treatment was effective and safe in our cases, with a very short hospitalization, no perioperative complications, and good results after 1-year followup. We chose stent-graft repair in our patients for the following reasons: the aneurysmal deterioration was restricted to a limited, short portion of the allograft; the anastomosis was not involved; the aneurysmal dilatation was at a distance from the flexion area of the knee; and there were no biological or clinical signs of infection.…”
Section: Discussionmentioning
confidence: 52%
“…1,2 As a consequence, less invasive endovascular approaches have been reported, with mixed results. [3][4][5][6] Most of these procedures consist of stent graft exclusion of the fistula. Antoniou et al 7 systematically reviewed such cases and found 41 patients in 33 reports published from 1990 to 2008 who were treated with stent graft exclusion.…”
Section: Discussionmentioning
confidence: 99%